Diffusion-model analysis of pPb and PbPb collisions at LHC energies - Schulz, Philipp; Wolschin, Georg (Arxiv, 2018)
We present an analysis of centrality-dependent pseudorapidity distributions of produced charged hadrons in pPb and PbPb collisions at the LHC energy of sqrt{s_NN}=5.02 TeV, and of minimum-bias pPb collisions at 8.16 TeV within the nonequilibrium-statistical relativistic diffusion model (RDM). In a three-source approach, the role of the fragmentation sources is emphasized. Together with the Jacobian transformation from rapidity to pseudorapidity and the limiting fragmentation conjecture, these are essential for modeling the centrality dependence. For central PbPb collisions, a prediction at the projected FCC energy of sqrt{s_NN}=39 TeV is made.
Gesehen am 20.08.2020